Utilization of delivery and postnatal health services by indigenous women of a hilly, remote district in India: a struggle for safe motherhood - Purohit, Neha (International Journal Of Community Medicine And Public Health, 2021)
Background: Maternal and new-born health remains issue of critical concern for the developing world. The day of Delivery and immediate postpartum period poses the greatest risk of survival for the mother as well as the child. The indigenous women in rural, remote areas face various geographical, climatic, socio-economic inequities, which further amplify health risks associated with delivery. The study aimed to identify the pattern of utilization of intrapartum and postpartum health services by indigenous women in rural, remote area and understand the challenges faced by them to access care. Methods: A community based descriptive, cross-sectional study was carried out in 41 far-flung villages of Lahaul and Spiti district in Himachal Pradesh, India, using a mixed-method approach of data collection. 103 females who had experienced delivery in past 2 years and were residents of Lahaul for minimum of 3 years, were interviewed using a semi-structured questionnaire. The quantitative data was analysed by SPSS-20. The qualitative data was transcribed and analysed thematically. Results: The study highlighted the significant physical, psychological, financial and socio-cultural risks borne by the women of Lahaul in order to access biomedical care during maternity care. The prime cause of the grave situation was inadequacy of appropriate care in the health facilities of the district, which forced the women to migrate to areas with better healthcare facilities. Conclusions: The study stressed the need to establish comprehensive emergency, obstetric and new born care in the tribal area to reverse the disparities in the region and improve health outcomes.